Investigating Ageing Process of Die Cast Aluminum in Squirrel Cage Rotors Exposed to Heavy-Duty Load Conditions - Pitis, Constantin; Al-Chalabi, Zaid (Journal of Environmental Science and Engineering Technology, 2017)
Most of the applications used in underground mining industries (explosion-proof environment) are performing in heavy-duty load conditions. As a result, standard designs of explosion-proof, water-cooled squirrel cage induction motors (WC-SCIM) equipped with standard designs of die-cast aluminium rotors (DCAR) are exposed to higher than expected rotor bar current values. Site investigations and dynamometer tests confirmed that severe heavy-duty loading induce high thermo-mechanical stresses (TMS) in DCARs. Frequent occurrences of such TMS (superimposed on the rated condition stresses) may bring conductive material (Aluminum) of the rotor bars to its fatigue conditions initiating rotor degradation process with subsequent influence on motor performances with consequent financial losses. The paper uses multidisciplinary techniques to study the ageing process of Die Cast Aluminum in Squirrel Cage Rotors Exposed to Heavy-Duty Load Conditions of a 50 hp SCIM equipped with DCAR. Based on claims regarding performance degradations, the research started with site measurements confirming the adverse heavy-duty load conditions. Statistic-probabilistic methods are used to determine Reliability indicators by using Fault Tree Method (FTM). The mathematical model confirmed the motor reliability and enable detection of weak points of the motor. Thermodynamic calculations are used to assess motor performances and its reliability by estimating air gap reduction and heat transfer to the bearings as the two major consequential effects of the TMS developed within DCAR. Dynamometer tests have been used to replicate the site conditions enabling creation of a mathematical model of thermal stress inside the rotor bars. After specific dynamometer tests a number of rotors have been cut-open to investigate the intimate rotor bar degradation. While there are various methods of detecting failed rotor bars, a Secondary research performed by authors indicate that to date no other research has been undertaken in studying this phenomenon.